Repetitions of violence in the works of Vitória Cribb and Welket Bungué - Cardoso, Eduardo Prado (2021)
The article describes three audiovisual pieces (@Ilusão, Bustagate and Eu Não Sou Pilatus, produced by Vitória Cribb and Welket Bungué, between 2019 and 2020). It discusses how they address, in their way, the repetition of violence against Black bodies in the digital environment of the web. As such, it invokes a qualitative and aesthetic analysis of the videos’ features and the spaces where they were found. Following Hui (2021), the paper explores the assumption that art can shed light on the irrationality that algorithms enable and reach the sublime, the non-rational. In doing so, the creative minds behind the works cited forge morethan escapist perspectives from reality to offer antiracist angles about the explicit irrationalityof violence — like in Bungué — or to model deformed algorithmic systems — like in Cribb.Thanks to the recursivity turned into artifacts, interpreting phenomena such as beatings and barbaric executions gains complex meanings: repetitions found in social life meet their audiovisual counterparts and create discourses via digital sharing. Besides holding accountable those who allow and disseminate such representations — in and out of the web—, the paper makes a case that the artists appropriate both in form and content certain social manifestations which perpetuate types of violence so that the online environment can also feature more reflection and dialogue.